EVALUASI PROGRAM PEMBELAJARAN KESETARAAN PAKET C DENGAN MODEL CIPP DI SATUAN PENDIDIKAN NON FORMAL SANGGAR KEGIATAN BELAJAR KOTA AMBON - Huberta Yempormase; Hermelina Abarua; Rosmarin Tutupary (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning is a process of interaction between students and educators in a designed learning environment to achieve specific educational goals. The success of a learning program depends on educators' ability, facilities, planning, implementation, and evaluation. Evaluation serves as a tool to measure learning objectives achievement and assess teaching method effectiveness. This research aims to evaluate the implementation of Paket C equivalence learning program using the CIPP model (Context, Input, Process, Product) at Non-Formal Education Unit of Learning Activity Center (SPNF SKB) in Ambon City. Using a qualitative descriptive approach with observation, interviews, and documentation methods, the study examined four aspects of the CIPP model. Results on the context aspect showed that the institution's vision and mission aligned with established objectives. In the input component, the curriculum was based on Permendikbud No. 12 of 2024, covering learning facilities, resources, and qualified human resources. The process component evaluated learning implementation including planning, execution, and assessment phases. The product component analyzed student achievement results through final grade records. The evaluation revealed that while the program generally followed established standards, several improvements were needed in learning facilities maintenance, teaching methods variation, and student engagement strategies to enhance overall program effectiveness.